THE INSTITUTIONAL DIMENSION OF BRITISH EUROSCEPTICISM: CONTEMPORARYSTATUS AND SPECIAL FEATURE OF DEVELOPMENT - Вахняк, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The concept «Euroscepticism» first appeared in the UK in the 70-ies of XX century, among the opponents of the country’s membership in the European Union. Today, the term «Euroscepticism» is used when we talk about negative and sceptic attitude to European integration. Besides the general non-acceptance of integration in the European Union, eurosceptics make a protest against separate spheres of community activities, against the introduction of the single currency “Euro”, construction of supranational entities and federalization. More and more the opponents of European integration speak in support of maintenance of nation states, their sovereignty and express concern that further integration eliminates national sovereignty of nation states. Today, the eurosceptics in UK take strong positions. Their political parties with their programs share common ideological views and beliefs. First, the British don’t share the ideas of creating a single European state, because countries with different traditions, cultural value and languages can be transformed into a homogeneous Union. In addition to the above, the eurosceptics are convinced that the European Union affects the political situation in the UK; they strongly oppose the country’s accession to the Euro area. Opponents of European integration assert that the sovereignty and liberty of Britain is limited to the activities of the institutions of the European Union, which increases their control from the national to the supranational level. As stated above the increase of Euroscepticism in the last decadepromoted to the emergence and development of many parties and organizations in Europe and in the UK with certain anti-European sentiments. These include: the British Conservative Party, the British National Party. The organizations of the Eurosceptic include: «The Bruges Group», «Business for Sterling», «Congress for democracy», «Europe of Nations», «the New Alliance» and «Free Britain». However, the main, the largest and most powerful party is United Kingdom Independence Party. In the UK, in the native country of euroscepticism, on 23 June 2016 took place a referendum of membership of the EU, and United Kingdom Independence Party became the head of the campaign of withdrawal from the European Union. So, today, euroscepticism includes all political forces, both the left and especially right, which don’t support or European idea, or its institutional embodiment. All these facts induce to more thorough and in-depth study of the causes, prerequisite of euroscepticism in member-countries of the EU, because the euroskeptics with every next election strengthen its position in the European Parliament. It may have a negative influence on the European integration policy of the European Union, what is not interested Ukrainian side.